Effect of green-manure dhaincha (Sesbaniu aculeata) and phosphorus on growth, yield and phosphorus uptake by - wheat (niticum aestivum) - RAJA RAM SAH; R.K. RAI; P.K. MUKHERJEE (Indian Journal of Agronomy, 2001)
An experiment conducted during the winter season of 1994-95 and 1995-96 showed that phosphorus application to green-manure crop of dhaincha (Sesbania aculeata) improved the growth and yield of wheat (Triticum aestivum L. emend. Fiori & Paol.) and P uptake. However, the yield attributes, dry-matter production and available N and P in soil were affected more conspicuously when P applied to green-manure crop at sowing than at burying and as a consequence, increased the grain yield. Green-manuring with 30 kg P205/ha at sowing followed by 60 kg P205/ha to wheat resulted in maximum net return of the sequence.